Causal effects for genetic variants of osteoprotegerin on the risk of acute myocardial infarction and coronary heart disease: A two-sample Mendelian randomization study - Chao, Peng; Zhang, Xueqin; Zhang, Lei; Cui, Xinyue; Wang, Shanshan; Yang, Yining (Frontiers in Cardiovascular Medicine, 2023)
Although since 1980s, the mortality of coronary heart disease has obviously decreased due to the rise of coronary intervention, the mortality and disability of coronary heart disease are still high in some countries. etiological studies of acute myocardial infarction (AMI) and coronary heart disease (CHD) are extremely important. In this study, we used TSMR method to collect GWAS statistics of OPG, AMI or CHD to reveal the relationship between OPG and these two diseases. We used TSMR method to investigate the causal relationship between OPG and cardiovascular diseases (including AMI and CHD). Overall, we obtained 7 AMI genetic variants and 7 LD-independent CHD genetic variants (r2<0.001). We found evidence that OPG genetic predisposition is beneficial to AMI.(IVW OR = 0.877; 95% CI = 0.787-0.977; P = 0.017; 7 SNPs) and CHD (IVW OR = 0.892; 95% CI = 0.803–0.991; P = 0.033; 7 SNPs). After removing the influence of rs1385492, we found that there was a correlation between OPG and AMI/CHD (AMI: weighted median OR = 0.818;95% CI = 0.724-0.950; P = 0.001; 6SNPs ;CHD :weighted median OR = 0.842; 95% CI = 0.755-0.938; P =1.893X10-3; 6SNPs). our results showed that OPG had a close genetic causal relationship with myocardial infarction or coronary heart disease, and this close causal relationship provided us with new ideas in the future research field of etiology of acute myocardial infarction and coronary heart disease.